Activity Based Costing Implementation to Determine MSME’s Cost Production - Angga Setiawan; Reswanda Reswanda (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
MSME’s are proven capable to survive after the crisis that occurred to maintain sustainability. In this global era, one of them is controlling costs, This study aims to determine the Cost Production of MSME’s Wader dan Olahan Sambal Bu Gito Surabaya located at Jl.Sidorukun 2 no.41, Surabaya for one month using the Activity Based Costing method to be more accurate in tracking Factory Overhead Costs based on activities related to production, this study used qualitative methods with a case study approach. The results of the study show that for Wader Original shows conditions under cost (6,05%), and for Wader Rempah Pedas, the same conditions are under cost (13,85%) compared to using traditional system. thus the use of ABC as a method of determining the cost production is more accurate, and can be applied by the company as a consideration making policies for the progress of companies and cost control procedures